2016
DOI: 10.5897/ajbm2016.8032
|View full text |Cite
|
Sign up to set email alerts
|

Foreign direct investment (FDI) and corruption: Is it a major hindrance for encouraging inward FDI?

Abstract: The study used panel data from 1998 to 2014 among 48 different countries to determine the relationship between foreign direct investment and corruption. For identifying the relationship, the study employed random effect model (REM), feasible general least squares method (FGLS) and panels corrected standard errors (PCSE). The results of the three panel estimation methods reveal that the variable of corruption is statistically significant at 1%, but negative relations between corruption and FDI results were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 63 publications
3
9
0
1
Order By: Relevance
“…According to Davidescu & Strat (2015), in Romania, during 2000-2010, there existed an unidirectional short-run causality running from FDI to the shadow economy and the relationship between FDI and the shadow economy was negative in a short-run. The the relationship between corruption and FDI was negative in 48 countries (Hossain, 2016). Similar results have been obtained by Canare (2017) and Hakimi & Hamdi (2017) in their studies: corruption had a negative effect on the FDI inflows and investment activities.…”
Section: Theoretical Backgroundsupporting
confidence: 84%
“…According to Davidescu & Strat (2015), in Romania, during 2000-2010, there existed an unidirectional short-run causality running from FDI to the shadow economy and the relationship between FDI and the shadow economy was negative in a short-run. The the relationship between corruption and FDI was negative in 48 countries (Hossain, 2016). Similar results have been obtained by Canare (2017) and Hakimi & Hamdi (2017) in their studies: corruption had a negative effect on the FDI inflows and investment activities.…”
Section: Theoretical Backgroundsupporting
confidence: 84%
“…Egger and Winner (2005) found corruption to be positively correlated with the level of FDI in the host country, while Gutierrez (2015) argues that corruption has no effect on FDI inflows because it concentrates on capital-intensive industries related to the exploitation of natural resources. Some studies have found that corruption has an adverse impact on FDI inflows (Wei, 2000;Ohlsson, 2007;Al-Sadig, 2009;Castro and Nunes, 2013;Khan, 2013;Quazi, 2014;Udenze, 2014;Hossain, 2016;Epaphra and Massawe, 2017). However, this means that countries which support anti-corruption measures will benefit more from increasing FDI inflows.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kebijakan tingkat bunga diharapkan menjadi sebuah instrumen yang efektif. Penelitian ini menganalisis pengaruh pertumbuhan ekonomi, tingkat bunga, dan CPI terhadap FDI di ASEAN-6 tahun 2004-2016 Investment is used to drive the domestic economy both in developed and developing countries. It can be done through direct investment or indirect investment.…”
unclassified
“…In addition, Siddiqui & Aumeboon-suke (2014) found that interest rate had a negative and significant impact on FDI. Quazi (2014) and Hossain (2016) argued that corruption had impact on FDI. Quazi (2014) suggested that governments should reduce the level of corruption and create a healthy economic environment to attract FDI.…”
mentioning
confidence: 99%
See 1 more Smart Citation